K-State First Co-Curricular Guide 2019 - Kansas State University, K-State First (Kansas State University, K-State First, 2019)
Co-curricular events have a huge impact on student learning and community building. Students often note that they remember these out of the classroom experiences as the time when they were most able to bond with their peers and connect what they were learning inside the classroom to their lives. This document provides general guidelines, information about funding, and event ideas for K-State First instructors.
Citation: K-State First (2019). K-State First Co-Curricular Guide 2019. Manhattan, Kansas: K-State First.
Keywords: Guide; Co-curricular; First-year experience program